Is Location Everything? Regulation of the Endothelial CCM Signaling Complex - Swamy, Harsha; Glading, Angela J. (Frontiers in Cardiovascular Medicine, 2022)
Recent advances have steadily increased the number of proteins and pathways known to be involved in the development of cerebral cavernous malformation (CCM). Our ability to synthesize this information into a cohesive and accurate signaling model is limited, however, by significant gaps in our knowledge of how the core CCM proteins, whose loss of function drives development of CCM, are regulated. Here, we review what is known about the regulation of the three core CCM proteins, the scaffolds KRIT1, CCM2, and CCM3, with an emphasis on binding interactions and subcellular location, which frequently control scaffolding protein function. We highlight recent work that challenges the current model of CCM complex signaling and provide recommendations for future studies needed to address the large number of outstanding questions.